Snowmen at night - Buehner, Caralyn; Buehner, Mark (New York : Phyllis Fogelman Books, 2004)
Snowmen play games at night when no one is watching.
Companion book to: Snowmen at Christmas.
G8
Keywords: Snowmen -- Fiction; Stories in rhyme